2017
DOI: 10.1111/add.13910
|View full text |Cite
|
Sign up to set email alerts
|

Mapping medical marijuana: state laws regulating patients, product safety, supply chains and dispensaries, 2017

Abstract: Aims 1) To describe open source legal datasets, created for research use, that capture the key provisions of U.S. state medical marijuana laws. The data document how state lawmakers have regulated a medicine that remains, under federal law, a Schedule I illegal drug with no legitimate medical use. 2) To demonstrate the variability that exists across states in rules governing patient access, product safety, and dispensary practice. Methods Two legal researchers collected and coded state laws governing marijua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 34 publications
0
59
0
2
Order By: Relevance
“…Another significant consideration is that the current study used smoked cannabis because this is the most common method of medical cannabis use [52]. However, the therapeutic utility of smoked cannabis may be limited by respiratory risks including chronic bronchitis [53], the presence of combustion by-products [54,55], a lack of regulation regarding medical cannabis strength (i.e., THC concentration) and other cannabinoid content [56], and subjective effects related to abuse liability which are not as apparent with other methods of administration (i.e., [47]). Adverse respiratory effects and combustion by-products would be avoided by vaporizing cannabis [61,63,64], while the superior bioavailability of THC afforded by the intrapulmonary route relative to oral administration would be preserved [57].…”
Section: Discussionmentioning
confidence: 99%
“…Another significant consideration is that the current study used smoked cannabis because this is the most common method of medical cannabis use [52]. However, the therapeutic utility of smoked cannabis may be limited by respiratory risks including chronic bronchitis [53], the presence of combustion by-products [54,55], a lack of regulation regarding medical cannabis strength (i.e., THC concentration) and other cannabinoid content [56], and subjective effects related to abuse liability which are not as apparent with other methods of administration (i.e., [47]). Adverse respiratory effects and combustion by-products would be avoided by vaporizing cannabis [61,63,64], while the superior bioavailability of THC afforded by the intrapulmonary route relative to oral administration would be preserved [57].…”
Section: Discussionmentioning
confidence: 99%
“…Unregulated "medical marijuana" use for pain covers multiple demographics and disorders, even reaching historically underserved groups such as seniors facing undertreatment of pain at end-oflife [23]. However, safety, efficacy, and consistency of plant-derived medicines such as medical Cannabis do not yet approach traditional pharmaceutical standards for widespread therapeutic deployment [16,[24][25][26][27][28]. Thus, there is a need for well-defined compositions of secondary metabolites from Cannabis that selectively relieve pain.…”
Section: Introductionmentioning
confidence: 99%
“…State medical marijuana laws differ along a variety of dimensions, which have been discussed at length in several prior studies (Bradford and Bradford, 2018;Klieger et al, 2017;Pacula et al, 2015;Pacula and Smart, 2017;Sabia and Nguyen, 2018;Wen et al, 2015). While little is known about the extent to which many of these dimensions are associated with access by recreational users (Pacula et al, 2015;Smart, 2016), those related to dispensaries have received the greatest research attention given their demonstrated association with changes in prices, potency and market size (Anderson et al, 2013;Sevigny et al, 2014;Smart, 2016).…”
Section: Background On Medical Marijuana Laws and Dispensariesmentioning
confidence: 99%
“…The rules and regulation surrounding the licensing of retail sale and distribution of medical marijuana has become more complex and burdensome. For example, the vast majority of states today regulate dispensary density, location and product source, while nearly half also regulate stocking levels (Klieger et al, 2017). Structural requirements for dispensaries, cultivators, and processors are also imposed, with regulations related to safety and security, ventilation systems, hand washing stations, and even disposal.…”
Section: Medical Marijuana Laws and Dispensaries Todaymentioning
confidence: 99%
See 1 more Smart Citation